2010
DOI: 10.1111/j.1750-3841.2010.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Composition and Antiproliferative Activities of Explosively Puffed Ginseng (Panax ginseng C.A. Meyer)

Abstract: The puffing process could provide an alternative mean to produce functional ginseng products, along with a reduction in processing time as compared to traditional red ginseng processing by steam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…The major active components of ginseng are ginsenosides. More than forty ginsenosides have, so far, been isolated and each ginsenoside possesses different pharmacological effects [11]. Commercially available Korean ginseng products are classified into fresh ginseng, white ginseng, and red ginseng.…”
Section: Discussionmentioning
confidence: 99%
“…The major active components of ginseng are ginsenosides. More than forty ginsenosides have, so far, been isolated and each ginsenoside possesses different pharmacological effects [11]. Commercially available Korean ginseng products are classified into fresh ginseng, white ginseng, and red ginseng.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ginsenosides (ginseng saponins) have been known as the main active components in ginseng. 8 Functional studies regarding red ginseng CH (RGCH) in which steamed soybean and red ginseng water extract are mixed prior to fermentation have never been reported. This study compared the possible antidiabetic and antihyperlipidemic effects of CH and RGCH in subjects with IFG for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that commercial red ginseng products could have AF and AFG levels ranging from 0.35 − 2.51 % and 0.25 − 2.64 %, respectively [8, 9]. The ginsenosides, which are better-known KRG components, have a content ranging from 0.5 − 1.1 % [8, 10]. …”
Section: Introductionmentioning
confidence: 99%